Odpowiedzi

2010-03-08T12:47:39+01:00
1a. -7x - 14 + 4 = -3x
-4x = 10
x = -2.5
b. 6x = 10
x = 1 i 2/3
c. (x-1)(x+1) = x(x+3)
x2 - 1 = x2 + 3x
3x = -1
x = -1/3
e. 2x + 4 + 6x + 12 = 0
8x = -16
x = -2
f. x2 - x = x2 + 3
-x = 3
x = -3
g. 4x - 8 / 12 - 3x-9 / 12 = x-1
x-17 / 12 = 12x - 12
- 11x = 5
x = -5/11

2a. -8x - 4 >/ (wieksze badz rowne) -x - 1
-7x >/ 3
x </ 3/7

x € ( - niesk. ; 3/7>

b. x2 + 4x + 4 - x2 + 4x - 4 < 0
8x < 0
x < 0

x€ ( - niesk. ; 0)

c. 3x > 6
x > 2
x€ (2; +niesk)

d. 4x - 1 > 3x
x > 1

x € (1; +niesk)

e. x € {1,2}
f. x € {0, 10}

3a. x=5-y
5-y-2y=1

x=5-y
-3y = -4

x=5-y
y = 1 i 1/3

x = 3 i 2/3
y = 1 i 1/3

b.

x-y = 4 | x3
3x-3y = 24

3x - 3y = 12
3x - 3y = 24 +

6x = 36
x = 6

6 - y = 4
y = 2

c.

2x - y + 2 = 2x
2x = -y

y = -2
x = -1

4.
x - 1sze naczynie
y - 2gie naczynie

x+y = 24
x - 3 = y + 3

x+y = 24
x = y + 6

2y = 18
x = y+6

y+9
x+15